IL-17 and IL-10 as potential biomarkers for diagnosing periodontitis patients: A Review - Abdulsalam Mohammed , Maha; Fadhil Abbas , Raghad (Diyala Journal of Medicine, 2023)
Background:Evaluation methods for periodontal disorders are continually being refined to yield more precise, reliable, and time-efficient findings. Radiographic reports and clinical assessments of periodontal tissues, which served as the basis for earlier trends, were used to identify disorders affecting the tooth-supporting structures. As traditional approaches have become more apparent gradually over time, new methods emerged, some of which have been empirically validated. One example is the detection and measurement of biomarkers in bodily fluids. One of the most pressing issues in periodontal field nowadays is the search for an idealized periodontal diagnostic/prognostic biomarker that can both identify diseased areas and track the therapeutic success of periodontal treatment. Both IL-17 and IL-10 have shown connection to periodontitis that could encourage using them as diagnostic tools. Objective: To provide a review of the role and association of the above biomarkers to periodontitis. Patients and Methods: A systematic research of Google scholar, Scopus, PubMed Central, research gate was conducted using keywords such as diagnosis, periodontitis, IL-17, IL-10, biomarkers, Saliva and gingival crevicular fluid (GCF). Results: out of 58 records which resulted from the initial search only 14 were included which used roles, associations, and diagnosis as their outcomes. Conclusion: Evidence from the selected records suggests that the above stated biomarkers might be able to discriminate periodontitis from health, monitoring disease progression and post treatment outcome, but actual clinical application needs much further research.